STRATEGI PENDIDIKAN ISLAM ANAK USIA DINI DALAM MEMBENTUK AKHLAK MULIA DAN KARAKTER RELIGIUS DI ERA DIGITAL - Tentiasih, Septyana; Ismail (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This study aims to examine the strategies implemented at Bustanul Aisyiyah Ketro 1 to develop noble character and religious identity in early childhood students in the digital era. A qualitative approach with a case study design was used to explore the phenomena in which the influence of digital devices poses specific challenges to character formation. Data collection techniques included interviews, observations, and documentation to obtain a comprehensive overview of the habituation method through memorization of daily prayers and hadiths, as well as parental involvement in supporting religious education at home. The findings reveal that habituation methods effectively foster religious character; however, the primary challenge of gadget influence necessitates preventive measures through restricted gadget use at school and parental support at home. This study recommends stronger collaboration between educational institutions and parents to optimize character education goals amidst digital challenges.